1989
DOI: 10.1002/pd.1970090803
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal detection of trisomy 9 mosaicism

Abstract: Chromosomal mosaicism in amniotic fluid cells poses a serious dilemma in prenatal diagnosis since the observation may represent: (1) pseudomosaicism--an inconsequential tissue culture artefact; or (2) true mosaicism--occurring in approximately 0.20 per cent of amniocenteses with a significant impact on pregnancy outcome. Mosaicism for trisomy 9 was observed in an amniotic fluid specimen obtained for advanced maternal age with two cell lines [46,XX (46 per cent)/47,XX, +9 (54 per cent)] present in each of four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 15 publications
4
20
0
Order By: Relevance
“…Schwartz et al [1989] reported a case of mosaic trisomy 9 diagnosed by amniocentesis in which 46% of amniocytes, but only 1 of 50 fetal lymphocytes, were trisomic. In the case of Sherer et al [1992], trisomy 9 was identified by amniocentesis in all cells from all colonies and cultures, but no trisomy 9 cells were found in newborn cord or peripheral blood.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Schwartz et al [1989] reported a case of mosaic trisomy 9 diagnosed by amniocentesis in which 46% of amniocytes, but only 1 of 50 fetal lymphocytes, were trisomic. In the case of Sherer et al [1992], trisomy 9 was identified by amniocentesis in all cells from all colonies and cultures, but no trisomy 9 cells were found in newborn cord or peripheral blood.…”
Section: Discussionmentioning
confidence: 98%
“…Four prenatally diagnosed cases which did not result in term birth were also reviewed and will be discussed, but were not included in the data analysis [Franke et al, 1975;Frohlich, 1982;Schwartz et al, 1989;Zadeh et al, 19871. Survival, gestational age at birth, parental ages, birth weight and head circumference, and incidence of various congenital anomalies were compared among mosaic and nonmosaic cases using chi-square analysis, Student's t-test, or Fisher's exact test where appropriate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the available literature on trisomy 9 focuses on reports concerning results of prenatal testing including sonographic findings [e.g., Francke et al, 1975;Schwartz et al, 1989;Benacerraf et al, 1992;Saura et al, 1995] or fetal autopsy [Chitayat et al, 1995]. Schwartz et al [1989] describe the physical characteristics in a fetus with trisomy 9 mosaicism including micrognathia, skeletal malformations and cardiac malformations.…”
Section: Introductionmentioning
confidence: 99%
“…Schwartz et al [1989] describe the physical characteristics in a fetus with trisomy 9 mosaicism including micrognathia, skeletal malformations and cardiac malformations. Similar findings are found in a study by Smoleniec et al [1993] in a pregnancy that was electively terminated.…”
Section: Introductionmentioning
confidence: 99%